Novel Multifunctional and Multitarget Homo- fe2 and Heterobimetallic [(Fe,M) with M = Re or Mn] Sulfonyl Hydrazones - Silva-Molina, C; Silva-Molina, C (Royal Society of Chemistry, 2020)
The synthesis and characterization of the novel ferrocenyl sulfonyl hydrazide [Fe(η5-C5H5){(η5-C5H4)-S(O)2-NH-NH2}] (2) is reported. Additional studies on its reactivity using acetone or the ferrocenyl-, cyrhetrenyl- or cymantrenyl-aldehydes have allowed us to isolate and characterize [Fe(η5-C5H5){(η5-C5H4)-S(O)2-NH-NCMe2}] (3), the bis(ferrocenyl) derivative [Fe(η5-C5H5){[(η5-C5H4)-S(O)2-NH-NCH-(η5-C5H4)]Fe(η5-C5H5)}] (4) and the heterodimetallic compounds [Fe(η5-C5H5){[(η5-C5H4)-S(O)2-NH-NCH-(η5-C5H4)]M(CO)3}] with M = Re (5a) or Mn (5b). The X-ray crystal structures of compounds 3, 5a and 5b are also reported. A comparative study of their electrochemical and spectroscopic properties is also described. Additional computational calculations based on the DFT methodology have allowed us to elucidate the effect produced by the replacement of the terminal -NH2 (in 2) by the -NCMe2 (in 3) and -NCHR (in 4, 5a and 5b) moieties on the electronic distribution and to explain the differences detected in their electrochemical properties and absorption spectra. In vitro cytotoxicity studies of compounds 2, 4, 5a and 5b on the HCT-116 (colon), MCF7 and MDA-MB231 (breast) cancer cell lines reveal that compound 2 has no significant activity (IC50 > 100 μM), while its derivatives 4, 5a and 5b proved to be active in the three cancer cell lines selected in this study. The growth inhibition potency of compounds 5a and 5b against the triple negative MDA-MB231 breast cancer cell line is similar (or slightly) greater than that of cisplatin. Moreover, compounds 2, 4, 5a and 5b are less toxic than cisplatin in the normal and non-tumoral BJ fibroblasts, and the heterodimetallic complexes 5a and 5b with selective index >2.1 show an outstanding selective toxicity towards the MDA-MB231 cancer cells. © 2020 The Royal Society of Chemistry.